Deceptive Claims Using Fake News Advertising: The Impact on Consumers - Rao, Anita (Journal of Marketing Research, 2022)
Fake news advertising—advertising that mimics legitimate news articles—can be harmful if it misleads consumers to take actions they otherwise would not have taken (e.g., purchase an inferior product). However, little is known about whether fake news ads bring in new customers or are merely viewed by people already in the market for the advertised products. The author exploits a Federal Trade Commission–enabled shutdown of fake news advertisements for various products such as acai cleanses and teeth whiteners (but where the product sites continued to remain operational) to identify the extent of consumer interest in the presence and absence of fake news advertising. The findings indicate that interest wanes after the shutdown of fake news advertising, with the probability of a product site not receiving any new visits increasing by 22%. The overall decline in visits caused by the absence of fake news ads occurs despite some substitution by consumers to regular advertisements.